Design and Analysis of Single-Tuned Passive Filters for Total Harmonic Distortion (THD) Mitigation and Power Quality Enhancement - Shrestha, Sulav; Poudel, Sagar; Ghimire, Sajesan (Journal of Engineering and Sciences, 2025)
Harmonic distortion caused by nonlinear loads is a significant challenge in power systems, often resulting in reduced efficiency, overheating, and equipment malfunction. Despite the availability of various mitigation techniques, many fail to offer a cost-effective and practical solution for distribution networks. This research addresses that gap by designing and analyzing a five-stage single-tuned passive filter (STPF) system to mitigate harmonics in a 400V, 50Hz distribution network. The main objective is to reduce Total Harmonic Distortion (THD) in voltage and current to meet IEEE 519-2022 standards. The proposed filter system targets the 5th, 7th, 9th, 11th, and 13th harmonic orders using a simulation model developed in MATLAB/Simulink. The system initially showed high THD levels of 16.06% in voltage and 17.57% in current. After applying the filters, the voltage THD was reduced to 3.89%, and the current THD dropped to 2.52%. These results confirm the effectiveness of STPFs in improving power quality under nonlinear loading conditions.